Comparative Study of Three Different Topologies of Five-Level Inverter with SPWM Modulation Technique - Nabil Farah; Jurifa Bt. Mat Lazi; MHN Talib (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Multilevel Inverter (MLI) has attracted a great attention by different researchers and industries due to its capability in handling high power application and minimizing the harmonics contents in the output. This study propose three different topologies of MLI (5-level) which are Cascaded H-Bridge Multilevel Inverter (CHMLI) ,Diode Clamped Multilevel Inverter and Flying Capacitor Multilevel Inverter (FCMLI) .These three topologies have been modelled in MATLAB/SIMULINK and compared in terms of THD and number of components used. Sinusoidal Pulse Width Modulation is utilized to control both of the topologies with same DC source. The results showed that ,CHMLI is superior compared to DCMLI and FCMLI in which the CHMLI produce 26.29% THD while DCMLI and FCMLI produce 29.14% and 33.53% respectively .Moreover less components and switching losses is obtained when using the CHMLI.